9.3k views
3 votes
Question is below (wasn't sure about the answer)

Question is below (wasn't sure about the answer)-example-1
User Jill Cheng
by
5.4k points

1 Answer

3 votes

Answer: Choice A)


H = (SA)/(2(L+W)) - (LW)/(L+W)\\\\

=================================================

Work Shown:


SA = 2(LW + LH + HW)\\\\2(LW + LH + HW) = SA\\\\LW + LH + HW = (SA)/(2)\\\\LH + HW = (SA)/(2) - LW\\\\H(L + W) = (SA)/(2) - LW\\\\H = ((SA)/(2) - LW)/((L + W))\\\\H = (SA)/(2(L+W)) - (LW)/(L+W)\\\\

This is not the only way to solve for H.

User Cmonkey
by
5.4k points